2015
DOI: 10.1590/1678-775720150084
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity, physical and chemical properties of MTA mixed with propylene glycol

Abstract: Objective To investigate the physical (setting time, hardness, flowability, microstructure) and chemical (pH change, calcium release, crystallinity) properties and the biological outcomes (cell survival and differentiation) of mineral trioxide aggregate (MTA) mixed using different proportions of propylene glycol (PG) and water.Material and Methods White MTA was mixed with different water/PG ratios (100/0, 80/20 and 50/50). Composition (XRD), microstructure (SEM), setting time (ASTM C266-13), flowability (ANSI/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 25 publications
1
40
0
1
Order By: Relevance
“…It is the safest bioactive cements that exhibits the least discoloration and calcification of the tooth and pulp chamber, respectively [ 4 , 5 ]. These bioactive cements can induce higher expression of several genes (e.g., bone sialoprotein, dentin sialophosphoprotein, alkaline phosphatase, osteocalcin) and phosphatase activity, hence, stimulating biomineralization [ 6 , 7 , 8 , 9 ]. Nonetheless, these cements may present some clinical disadvantages, such as long setting time and modest physico-mechanical properties [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is the safest bioactive cements that exhibits the least discoloration and calcification of the tooth and pulp chamber, respectively [ 4 , 5 ]. These bioactive cements can induce higher expression of several genes (e.g., bone sialoprotein, dentin sialophosphoprotein, alkaline phosphatase, osteocalcin) and phosphatase activity, hence, stimulating biomineralization [ 6 , 7 , 8 , 9 ]. Nonetheless, these cements may present some clinical disadvantages, such as long setting time and modest physico-mechanical properties [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the comparison of the two surfaces effects, quantitative RT-PCR showed significant difference between the expression of RUNX2 only after 21 days of culture RUNX2 is an important transcriptional modulator of osteoblast differentiation, maturation and homeostasis, it showed that its role is in the earlier stages of multipotent stem cell activation and differentiation towards the osteoblast lineage 36) even if several studies underline that an appreciable increase of RUNX2 gene expression is generally recognizable after two weeks of culture 37,38) . In our experimental model an increase of RUNX2 gene expression, detectable 39) .…”
Section: Discussionmentioning
confidence: 98%
“…This optimized cement achieved an initial setting time of 10 min which was longer than DCS1 (6.5 min) and final setting time of 15 min which was shorter than DCS1. Another study conducted by Natu et al 39 who incorporated propylene glycol into MTA to improve its properties and found that the handling properties were improved, but the initial setting time was prolonged (18 min). Dubey et al 40 investigated the incorporation of graphene nano sheets into Biodentine and Endocem Zr and found that the setting time was shortened at 1% and 3% concentrations.…”
Section: Discussionmentioning
confidence: 99%